INVESTIGATION ON EFFECT OF CSR ON PERFORMANCE QUALITY: A CASE STUDY OF EFFAT UNIVERSITY, JEDDAH, KINGDOM OF SAUDI ARABIA - Duaa Mujalli; Ahmed Attia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aimed to determine the relationship between corporate social responsibility (CSR), internal quality performance (IQP) which was operational performance and external quality performance (EQP) which was organizational performance of EFFAT University in Jeddah, Saudi Arabia. This study had used mixed method and tools had been used to gather data. The primary data was collected through interview and questionnaire the secondary data was collected through previous study, technical journals, newspapers, books, research publication and report. The interview was semi-structured to gain feedback and comments on the study findings. The sample size were 150 employees which selected through simple random sampling. Furthermore, the study was used SPSS program to analyse the data. The result indicated that there was positive relationship between CSR and internal quality performance (IQP). Besides, there also positive relationship between CSR and EQP and between internal quality performance and external quality performance.